Tekst op voorzijde: 'Te 's-Hertogenbosch overleden op 20 februari 1925. Zijn geest van groote offervaardigheid blijve immer bij ons.'
Tekst op voorzijde: 'Te 's-Hertogenbosch overleden op 20 februari 1925. Zijn geest van groote offervaardigheid blijve immer bij ons.'.